Histological assessment of the phytohemagglutinin (PHA) skin test as a method to evaluate inflammatory response and cell mediated immunity in Magellanic penguins (Spheniscus magellanicus) - Ruoppolo, V.; Ribeiro, J. D.; Vanstreels, R. E. T.; Hurtado, R.; Pedron, B.; Cortopassi, S. R. G.; Catão-Dias, J. L. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
To quantify cell-mediated immunity in immunoecology the phytohaemagglutinin-induced skin-swelling test is one of the most employed assays, especially for wild birds. The PHA induced skin swelling is the most widely used method to measure cell-mediated immunocompetence in birds. The objective of this study was to contribute to understanding the factors that modulate susceptibility, pathogenesis and severity of infectious diseases and inflammatory response in Magellanic penguins through evaluation of an immunological test that can measure cellular responses.